2022
DOI: 10.3389/fphar.2022.1037239
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics-based population pharmacokinetic analysis and dose optimization of valproic acid in Chinese southern children with epilepsy: Effect of ABCB1 gene polymorphism

Abstract: Objective: The aim of this study was to establish a population pharmacokinetic (PPK) model of valproic acid (VPA) in pediatric patients with epilepsy in southern China, and provide guidance for individualized medication of VPA therapy.Methods: A total of 376 VPA steady-state trough concentrations were collected from 103 epileptic pediatric patients. The PPK parameter values for VPA were calculated by using the nonlinear mixed-effects modeling (NONMEM) method, and a one-compartment model with first-order absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 64 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…A study in a Tunisian population showed that the TT genotypes of C1236T, G2677T and C3435T were associated with DRE [25]. In addition, in our previous study, the rs3789243 variant of ABCB1 was found to have a significant effect on the pharmacokinetic variability of VPA, which was observed by establishing a population pharmacokinetic model [26].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…A study in a Tunisian population showed that the TT genotypes of C1236T, G2677T and C3435T were associated with DRE [25]. In addition, in our previous study, the rs3789243 variant of ABCB1 was found to have a significant effect on the pharmacokinetic variability of VPA, which was observed by establishing a population pharmacokinetic model [26].…”
Section: Introductionmentioning
confidence: 75%
“…There were no significant differences in the clinical characteristics of the patients in the persistent seizure and seizure-free groups. The selection of the two polymorphisms was based on previous reports suggesting their association with ASM responsiveness [23][24][25][26]. The polymorphism of ABCB1 rs1128503 as well as a haplotype consisting of the two SNPs were found to be associated with the efficacy of VPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Shen et al reported pharmacogenetics-based population pharmacokinetic analysis and dose optimization of valproic acid in Chinese southern children with epilepsy: Effect of ABCB1 gene polymorphism. 40 Thyssen et al reported population pharmacokinetics and Monte Carlo simulations demonstrated similar pharmacokinetics of risperidone in children, adolescents and adults. 41 Chen et al reported population pharmacokinetics and dose simulation of oxcarbazepine in Chinese paediatric patients with epilepsy.…”
Section: Discussionmentioning
confidence: 97%
“…Excipients can enhance solubility and bioavailability, improving absorption and pharmacokinetics. Enteric coatings can protect VPA from gastric degradation, reducing gastrointestinal side effects [12] .…”
Section: Introductionsmentioning
confidence: 99%